A current perspective on the compensatory effects of urea and methylamine on protein stability and function. Issue 2 (November 2015) - Rahman, Safikur; Warepam, Marina; Singh, Laishram R.; Dar, Tanveer Ali
Abstract: Urea is a strong denaturant and inhibits many enzymes but is accumulated intracellularly at very high concentrations (up to 3–4 M) in mammalian kidney and in many marine fishes. It is known that the harmful effects of urea on the macromolecular structure and function is offset by the accumulation of an osmolytic agent called methylamine. Intracellular concentration of urea to methylamines falls in the ratio of 2:1 to 3:2 (molar ratio). At this ratio, the thermodynamic effects of urea and methylamines on protein stability and function are believed to be algebraically additive. The mechanism of urea-methylamine counteraction has been widely investigated on various approaches including, thermodynamic, structural and functional aspects. Recent advances have also revealed atomic level insights of counteraction and various molecular dynamic simulation studies have yielded significant molecular level informations on the interaction between urea and methylamines with proteins. It is worthwhile that urea-methylamine system not only plays pivotal role for the survival and functioning of the renal medullary cells but also is a key osmoregulatory component of the marine elasmobranchs, holocephalans and coelacanths. Therefore, it is important to combine all discoveries and discuss the developments in context to physiology of the mammalian kidney and adaptation of the marine organisms. In this article we have for the first time reviewed all major developments on urea-counteraction systems to date. We have also discussed about other additional urea-counteraction systems discovered so far including urea-NaCl, urea-myoinsoitol and urea-molecular chaperone systems. Insights for the possible future research have also been highlighted.